KINERJA GURU BERSERTIFIKASI DALAM MENINGKATKAN MANAJEMEN MUTU PENDIDIKAN DI MADRASAH IBTIDAIYAH MUHAMMADIYAH SUDUNG KEDUNGTUBAN BLORA TAHUN 2015 - Sudarno Shobron; Suyanto Suyanto (Universitas Muhammadiyah Surakarta, 2016)
The performance of school teachers be one of the important factors in improving theschools quality. Certified teachers in Ibtidaiyah Elementary School of Muhammadiyah SudungBlora include planning and implementation of education quality development has been carriedout effectively and efficiently. It is characterized by the realization of the development of theimplementation of learning and learning outcomes in accordance with the vision and missionof the madrassa. support Factor in improving education quality management are 1) Availabilityof adequate learning media and support ongoing learning activities; 2) The interest andenthusiasm of students is increasing in participating in learning activities; 3) Preparation ofteachers in teaching is increasing; 4) The climate in the classroom learning environment moreconducive; 5) There is full support of the school community, society, and government; 6) Suppliedfacilities for picking up the students to and from school by teachers. Inhibiting factors inimproving the quality of education management in MI Muhammadiyah Sudung are 1) Lackof facilities to support the library and its contents; 2) Many teachers who are still miss match(not in accordance with the latest science education qualifications); 3) Lack of infrastructureeg. UKS room, and laboratory, so it is still a hard time in learning practices.Keywords: teacher performance; certification; management quality; education.Abstrak: Kinerja guru disekolah menjadi salah satu faktor penting dalam meningkatkanmutu sekolah. Guru bersertifikasi di Madrasah Ibtidaiyah Muhammadiyah Sudung KabupatenBlora meliputi perencanaan dan pelaksanaan pengembangan mutu pendidikan telahdilakukan secara efektif dan efisien. Hal ini ditandai dengan terwujudnya pengembanganpelaksanaan pembelajaran dan hasil pembelajaran sesuai dengan visi dan misi madrasah. Fakorpendukung dalam meningkatkan manajemen mutu pendidikan ialah 1) Tersedianya mediapembelajaran yang memadai dan menunjang berlangsungnya kegiatan belajar mengajar; 2)Minat dan semangat siswa semakin meningkat dalam mengikuti kegiatan pembelajaran; 3)Persiapan guru dalam pembelajaran semakin meningkat; 4) Iklim lingkungan belajar dalamkelas yang semakin kondusif; 5) Adanya dukungan penuh dengan warga sekolah, masyarakat,dan pemerintah; 6) Disediakan fasilitas antar jemput siswa saat berangkat dan pulang sekolaholeh guru-guru. Faktor penghambat dalam meningkatkan manajemen mutu pendidikan di MIMuhammadiyah Sudung ialah 1) Kurangnya fasilitas pendukung perpustakaan beserta isinya;2) Tenaga pengajar masih banyak yang miss match (tidak sesuai dengan kualifikasi ilmupendidikan terakhir); 3) Kurangnya sarana prasarana misalnya ruangan UKS, dan laboratorium, sehingga masih kesulitan saat praktek pembelajaran.Kata Kunci: kinerja guru; sertifikasi; manajemen mutu; pendidikan.